A multidrug-resistant Staphylococcus epidermidis clone (ST2) is an ongoing cause of hospital-acquired infection in a Western Australian Hospital - Widerström, M.; McCullough, C.; Coombs, Geoffrey; Monsen, T.; Christiansen, K. (2012)
We report the molecular epidemiology of 27 clinical multidrug-resistant Staphylococcus epidermidis (MDRSE) isolates collected between 2003 and 2007 in an Australian teaching hospital. The dominant genotype (sequence type 2 [ST2]) accounted for 85% of the isolates tested and was indistinguishable from an MDRSE genotype identified in European hospitals, which may indicate that highly adaptable health care-associated genotypes of S. epidermidis have emerged and disseminated worldwide in the health care setting. Copyright © 2012, American Society for Microbiology. All Rights Reserved.